Tangential Flow Filtration Technique: An Overview on Nanomedicine Applications - Musumeci, Teresa; Leonardi, Antonio; Bonaccorso, Angela; Pignatello, Rosario; Puglisi, Giovanni (Pharmaceutical Nanotechnology, 2018)
Purification is a key step for different types of approaches, ranging from food, biotechnology to pharmaceutical fields. In biotechnology, tangential flow filtration (TFF) allows obtaining the separation of different components of cells without instability phenomena. In the food industry, TFF ensures the removal of contaminants or other substances that negatively affect visual appearance, organoleptic attributes, nutritional value and/or safety of ailments. In the pharmaceutical area, purification is also an important and necessary step controlling the quality of final product. In the field of research and development of nanomedicines, several techniques are used to purify and/or to concentrate the batches for in vitro and in vivo applications. Despite many approaches that exist; current data reveal continued unsatisfactory results. Between them, TFF showed promising results, even if, currently, its use is uncommon if compared with other purification techniques usually reported in “materials and methods” sections. This review represents an overview of the different applications of TFF from protein purification to food application, with particular attention to the field of nanomedicine from polymeric to metallic nanoparticles, highlighting advantages and dis-advantages in the use of this technique. The theoretical aspect of the process has been examined.
Keywords: layer by layer method